PENDIDIKAN SEKS PENERAPAN DI SDIT BUNAYYA PADANGSIDIMPUAN - Mira Rahmayanti Sormin; Rosmaimuna Rosmaimuna; Darliana Sormin (Universitas Muhammadiyah Tapanuli Selatan, 2019)
Sex education is very important and needed by everyone, regardless of their educational status, employment, social status, and so on. Sex education must begin at home where parents are the first teachers. Many parents who give up their children's sex education at school even some parents who do not care even do not want to know at all. Parents should prepare from the beginning about this education in family life by working together and working hand in hand to educate their sons and daughters so that understanding and practice appear appropriate in accordance with Islamic education. So the family is the main actor in conducting sexual guidance against children. However, it cannot be denied that the school as an educational institution also has a very large contribution to the sexual education of their students. Considering that at present most of the children's activities are carried out in the school environment. So parents and schools must work together in giving children a correct understanding of sex education.Keywords: forerunner, education, sex